Poéticas do artista-professor: discursos e práticas na educação básica - Gomes, Diego Ribeiro (2023)
The present research aims to analyze the artistic/poetic production of the artist-teacher Adriano Carraretto, who works in basic education, problematizing his political-pedagogical work in art teaching, tracing his individual trajectory, along a restless and imprecise path, in search of fundamental reflection for the act of creation and the construction of knowledge in art. It is anchored in the investigative practice of Art-Based Educational Research (PEBAs) in an A/r/tography approach, where the artist-researcher-teacher departs from the imagery artistic form through theoretical search. Using multidisciplinary bibliographical review and qualitative-narrative interviews as techniques, in order to think about the relationship between discourse, poetics and pedagogical practice, which are sometimes antagonistic in the reality of times, spaces and materials used in education, problematizing the work of art teaching and artistic production.